The boom-bust cycle in Finland and Sweden 1984-1995 in an international perspective - Jonung, Lars.; Schuknecht, Ludger; Tujula, Mika.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2005)
This paper compares the boom-bust cycle in Finland and Sweden 1984-1995 with the average boom-bust pattern in industrialized countries as calculated from an international sample for the period 1970-2002. Two clear conclusions emerge. • First, the Finnish-Swedish experience is much more volatile than the average boom-bust pattern. This holds for virtually every time series examined. • Second, the bust and the recovery in the two Nordic countries differ markedly more from the international pattern than the boom phase does. The bust is considerably deeper and the recovery comes earlier and is more rapid.
Economic Papers